KONTRIBUSI SERAT LIMBAH BAN BEKAS KENDARAAN TERHADAP KUAT TARIK BELAH BETON - Muhajir Muhajir; Imransyah Idroes; Bunyamin Bunyamin (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2022)
In today's modern era, technological developments are needed to increase development in all fields. to provide flexibility and to prevent cracks in the concrete due to loading, because used tire fibers have a fairly high elastic modulus of 0.77 - 1.13 MPa, and a low density ranging from 1.08 - 1.27 tons/m3, and waste tires taken from PT. Kharindo Prakarsa, Sidoarjo Regency, East Java. The methods used are ACI 211.1-91 and ASTM C-33. The test object used is a cylinder with dimensions of 15 cm x 30 cm with a total of 20 specimens and a design FAS of 0.50. The test will be carried out until the concrete is 28 days old in an immersion bath. The results obtained from this study are the compressive strength of the control test object produced is 29.78 Mpa, and the value of the split tensile strength of concrete using the addition of used tire fibers with percentages of 0%, 0.5%, 1.0% and 1.5%. namely 3.88, 3.93, 3.96, and 4.07 MPa. Meanwhile, the determinant value (K) using linear regression analysis is 0.87, 0.81, 0.92, and 0.94, and the planned quality correlation (fct) with the test results obtained using correlation (fctcorrelation) is obtained values of 4.75, 4.44, 5.04 and 5.13, so that the difference between the correlation fct minus the 2013 fctSNI is 1.27, 2.02, and 4.67, then the comparison of fctSNI2013 testing fct correlation fct is obtained, so the correlation value is of all the percentages of fiber addition used tires are categorized as high, namely 0.81-0.99